FILOSOFI KENDO MASYARAKAT JEPANG: ADAPTASI DAN RE-MODELING PENDIDIKAN DAN PEMBANGUNAN KARAKTER BAGI GENERASI MUDA DI INDONESIA - Hastangka Hastangka; Rahma Fitriana; Latifa Nuraini (Waskita: Jurnal Pendidikan Nilai dan Pembangunan Karakter, 2022)
The concept and philosophy of character education that has developed so far have adopted many thoughts and concepts created by western culture and religion. This article discusses the concept and philosophy of character education created in Japan and rooted in the local culture. The method used in this study is a literature review and phenomenological research on the author’s experience while in Japan. The result of this study shows that the philosophy of Kendo has become a drive for character development (Tatemono no takucho) of Japanese youth. Japan can be an inspiration for the process of adaptation and remodeling of character education and development in Indonesia as the essence of the knowledge (Chisiki) about the character is based on the local culture.